MEASUREMENT OF K₀- FACTORS FOR SOME ELEMENTS IN PROMPT GAMMA NEUTRON ACTIVATION ANALYSIS - LE , THI QUYNH HUONG; PHAM , NGOC SON (Nuclear Science and Technology, 2013)
In Prompt Gamma Neutron Activation Analysis (PGNAA), the k0 standardization method has been proven to be useful in multiple element determination. Measurement and verification of Prompt-k0 data for use as standards are needed. The filtered thermal neutron beam and the PGNAA facility at the Dalat Nuclear Research Institute have been used to determine the Prompt-k0 factors for Cl, H, Fe, K, Cr, Na, Cu, Ti, Hg, C, Sm and Gd isotopes. The absolute efficiency curve of the HPGe detector was calibrated for a large energy range from 121.8 keV to 7790.2 keV by using the standard prompt gamma-rays spectrum from 35Cl (n,g)36Cl and the gamma-rays spectrum from 152Eu radioactive source. The present results of Prompt-k0 factors have been experimentally determined with an accuracy of 3.0% or better. These results are in a good agreement with those measured at other facilities.